The Significance of Agricultural Extension Activities for Wetland Rice Farmers in Serang, Indonesia - Noviyanti, Eka; Salampessy, Yudi L.A (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
In the context of Serang, Indonesia, agricultural extension activities have recently faced challenges related to reduced participation, as observed by the majority of agricultural extension officers. This reduced participation manifests through the limited attendance of farmers in meetings, the passive engagement of farmers and their respective groups in facilitating extension activities, and the generally muted response to agricultural technology content presented during these sessions. Conversely, fostering greater participation in agricultural extension activities can be achieved through coordinated efforts with supportive assistance or the provision of incentives. This study aims to assess the significance of agricultural extension activities for wetland rice farmers in Serang, Indonesia. It adopts a qualitative research approach, focusing on the phenomenology of extension activities within the realm of rice farming in Serang. Data analysis for this study employs Husserl's transcendental phenomenology data analysis method, which is incorporated within the interactive model data analysis framework. The information pertaining to the experiences of agricultural extension activities, as recounted by the informants (farmers), was extracted by identifying specific statements made by the farmer informants during interviews. A total of 133 individual verbatim statements provided by informants were systematically categorized. Three overarching themes, or units of meaning, emerged from this categorization, revealing the essence of agricultural extension activities and the informants' perceptions. These themes are as follows: Extension as a Source of Information, Extension as a Source of Technology, and Extension as a Source of Assistance. They encapsulate the texture and structure of the farmers' experiences with rice farming extension activities. The textural description highlights aspects closely linked to the transmission of information, technology, government initiatives, and assistance delivery. The structural aspect examines the meaning of extension activities within the economic, learning, and participation contexts of the participants. Subsequently, the combined meaning and essence of the rice farming extension experiences for each farmer informant are synthesized, collectively painting a comprehensive picture of their experiences. These experiences extend beyond the acquisition of agricultural knowledge and technology; they also encompass the provision of much-needed assistance for farmers to effectively adopt and implement these innovations.